2007
DOI: 10.1111/j.1399-0012.2007.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green elimination but not bilirubin indicates improvement of graft function during MARS therapy

Abstract: Measurement of indocyanine green plasma disappearance rate (PDR(ICG)) has been suggested as a meaningful liver function parameter. However, there are only very limited data concerning its value in the monitoring of graft dysfunction (GDF) and primary non-function (PNF) especially during molecular absorbent recirculating system (MARS) therapy. This study was therefore performed to evaluate the diagnostic accuracy to detect and monitor GDF with the measurement of the PDR(ICG) in direct comparison with convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In this study, PDR values <16%/min were associated with a sharp increase in mortality to approximately 50%. More recently, ICG PDR was found to be superior to bilirubin or INR as an indicator of post‐operative liver failure after liver resection (25) or graft dysfunction following liver transplantation (26).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, PDR values <16%/min were associated with a sharp increase in mortality to approximately 50%. More recently, ICG PDR was found to be superior to bilirubin or INR as an indicator of post‐operative liver failure after liver resection (25) or graft dysfunction following liver transplantation (26).…”
Section: Discussionmentioning
confidence: 99%
“…40 A number of other studies have demonstrated an association between EAD, primary nonfunction, and ICG clearance, albeit using different methods of measurement (KICG, PDR, R15), different timings of measurement (60 min to postoperative day 3), and different cutoff values (PDR <10% to <18%) (Table 1). 23,39,[49][50][51][52] Clearly, a standardized method would be useful for comparison between studies.…”
Section: Icg Clearance For Posttransplant Assessment Of Graft Functionmentioning
confidence: 99%